Efficiency of complex physical rehabilitation at hypertensive illness of I degree on ambulatory-policlinic the stage - Buksha S.B; Shabashov S.V (Kharkov National Pedagogical University, 2012)
The results of application of аromatherapy with a massage and autogenic training are examined in a physical rehabilitation. In research took part men aged 50-55 years, sufferings hypertensive illness of the I degree. It is marked that major reason of development of hypertensive illness is a decline of motive activity of patients, susceptibility to the nervous overloads and stresses, unbalanced feed, violation of the mode of labour and rest. Application of complex physical rehabilitation is recommended: medical gymnastics with the elements of the autogenic training, аromatherapy with a massage, dietotherapy, physiotherapy.